DIGITAL TRANSFORMATION AND ITS IMPACT ON SPEECH ETIQUETTE: A COMPARATIVE STUDY OF UZBEK AND ENGLISH (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article delves into the transformative effects of digital communication on the expression of speech etiquette in Uzbek and English languages. As technology reshapes the landscape of interpersonal interactions, this study seeks to explore the nuances of linguistic politeness, formality, and respect in the digital realm. By undertaking a comparative analysis, we aim to unravel the cultural intricacies that manifest in online communication, providing insights into the evolving dynamics of speech etiquette in the digital age.